2022
DOI: 10.1097/md.0000000000028499
|View full text |Cite
|
Sign up to set email alerts
|

Obesity or increased body mass index and the risk of severe outcomes in patients with COVID-19

Abstract: Background: To assess the effect of obesity or a high body mass index (BMI) on the risk of severe outcomes in patients with coronavirus disease 2019 (COVID-19). Methods: Studies on the relationship between BMI or obesity and COVID-19 since December 2019. The odds ratio (OR) and weighted mean difference (WMD) with their 95% confidence intervals (CIs) were used to assess the effect size. Results: BMI was significantly increased in COVID-19 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 96 publications
0
19
2
Order By: Relevance
“…However, our current study contradicts the majority of previous studies showing that overweight and obese adults were associated with lower PA levels (Haynes et al, 2018). Pandemic situations could increase their awareness of the importance of PA during the pandemic since being overweight or obese is one of the important risk factors for COVID-19 severity (Pu et al, 2020;Robertson et al, 2022;Yang et al, 2022). In addition, their perception of having more spare time during the pandemic could also facilitate them to do more PA (Robertson et al, 2022).…”
Section: Discussioncontrasting
confidence: 93%
“…However, our current study contradicts the majority of previous studies showing that overweight and obese adults were associated with lower PA levels (Haynes et al, 2018). Pandemic situations could increase their awareness of the importance of PA during the pandemic since being overweight or obese is one of the important risk factors for COVID-19 severity (Pu et al, 2020;Robertson et al, 2022;Yang et al, 2022). In addition, their perception of having more spare time during the pandemic could also facilitate them to do more PA (Robertson et al, 2022).…”
Section: Discussioncontrasting
confidence: 93%
“…These findings were supported by meta-analyses of data from Europe, Asia and North America [28] , [29] , [30] . Recent studies have again confirmed these findings, with a 2022 meta-analysis of 57 studies finding a doubling of hospitalisation risk in Western countries and a three-fold increased risk of severe disease in Asian populations among obese individuals [31] .…”
Section: Healthy Weight Maintenancementioning
confidence: 82%
“…Food can influence cytokine gene expression levels and thus modulate inflammation and oxidative stress[ 25 ]. Cytokines such as tumor necrosis factor (TNF)-alpha and IL-6 when produced excessively have been related to dysregulation of the inflammatory response and stimulation of cytokine storms[ 26 ]. Furthermore, increased adipose tissue contributes to greater leptin production, which is related to macrophage activation and proliferation, while reduced adiponectin levels decrease the synthesis of anti-inflammatory compounds.…”
Section: Influence Of Macronutrients On Covid-19 Severitymentioning
confidence: 99%